2017
DOI: 10.1002/14651858.cd012272.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for galactosaemia

Abstract: We were unable to identify any eligible studies for inclusion in this review and hence it is not possible to draw any conclusions based on randomised controlled studies. However, we are aware of uncontrolled studies which support the efficacy of newborn screening for galactosaemia. There are a number of reviews and economic analyses of non-trial literature suggesting that screening is appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
0
17
0
3
Order By: Relevance
“…It was shown to significantly reduce galactosemia‐related deaths, especially in the neonatal period (Ohlsson et al, 2012), however there is no controlled study in the literature reporting that it can prevent long‐term complications. (Schweitzer‐Krantz, 2003; Lak et al, 2017). Coss et al reported a series of 130 patients, 93.8% of which diagnosed by newborn screening and diet therapy initiated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to significantly reduce galactosemia‐related deaths, especially in the neonatal period (Ohlsson et al, 2012), however there is no controlled study in the literature reporting that it can prevent long‐term complications. (Schweitzer‐Krantz, 2003; Lak et al, 2017). Coss et al reported a series of 130 patients, 93.8% of which diagnosed by newborn screening and diet therapy initiated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the impact of newborn screening on the long-term outcome in galactosemia is still unclear. However, descriptive studies show its impact on mortality and acute symptomatology by favoring an early onset of nutritional management especially if results are available within the first week of life [87][88][89]. Moreover, early detection could have an effect on patient's quality of life.…”
Section: Newborn Screeningmentioning
confidence: 99%
“…Однако, несмотря на быстрое получение результатов неонатального скрининга, течение галактоземии может иметь раннюю манифестацию или приобретать злокачественный характер; кроме того, у недоношенных новорожденных клиническая симптоматика на начальном этапе весьма неспецифична. Следовательно, в части клинических случаев своевременная диагностика заболевания может представлять значительные трудности [26].…”
Section: клинические случаиunclassified